Insufficient investment into future growth: the forgotten cause of low growth in Germany - Karl Aiginger (Johannes Kepler University of Linz, Department of Economics, 2003)
There is a consensus that within the European Union, Germany is presently the country lagging farthest behind in terms of economic dynamics. Most researchers blame rising wages, welfare costs, and overregulated labour markets for this poor position. Some add that as a result of membership in the European Monetary Union, Germany lost the advantage of having low interest rates. To a certain extent, all view German unification as a prime culprit. This article acknowledges that although these factors have contributed to the recent underperformance of Germany, another major reason has been overlooked. A problem was brewing in Germany long before unification, namely the danger of being a high wage country specialised in medium technologies. We show that Germany neither increased its investment into research and education, nor did it embrace ICT technology. Germany lost its position as the European leader in research expenditures relative to GDP. For a set of 16 growth drivers, the dynamics of investment into research, education and information technology during the nineties were the slowest of all EU countries, and according to a quantitative indicator of total investment into the future Germany ranked second to last. Investment into future growth is specifically crucial when costs are high and markets are strictly regulated. Comparing the three potential reasons for low growth, namely underinvestment into growth drivers, rising costs and strict regulation, we find the first one to be the most important growth blocker and the least acknowledged in the German debate.
Keywords: E60; O11; O40; 330; The German problem; unification; labour market reforms; high tech industries; structural reforms; Agenda 2010